2012
DOI: 10.1590/s0100-69912012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do número de células caliciformes nas criptas da mucosa colônica com e sem trânsito intestinal

Abstract: OBJETIVO: Medir a espessura das criptas e quantificar o número de células caliciformes comparando a mucosa cólica com e sem trânsito intestinal, relacionando-as ao tempo de exclusão. MÉTODOS: Sessenta ratos Wistar, foram distribuídos em três grupos com 20 animais segundo a operação final para a retirada dos cólons, realizadas em seis, 12 ou 18 semanas. Em cada grupo, 15 animais foram submetidos à derivação do trânsito por colostomia proximal no cólon esquerdo e fístula mucosa distal e cinco apenas à laparotomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…13 It has also been demonstrated that an overproduction of OFR causes harm to the colonic mucosa, decreases the population of goblet cells, reduces the content and modifies the expression of mucins, causes disruption of protein constituents of intercellular junctions, and also causes oxidative damage to cellular DNA. 13,[15][16][17][27][28][29] All these findings confirmed the higher capacity of OFR production by colonic cells with metabolic changes, as shown by the relationship between an increased production of OFR and the disruption of different defense systems of epithelial barrier. 13 Based on these findings, several studies began to test the effectiveness of substances with antioxidant activity for the treatment of DC.…”
Section: Discussionsupporting
confidence: 69%
“…13 It has also been demonstrated that an overproduction of OFR causes harm to the colonic mucosa, decreases the population of goblet cells, reduces the content and modifies the expression of mucins, causes disruption of protein constituents of intercellular junctions, and also causes oxidative damage to cellular DNA. 13,[15][16][17][27][28][29] All these findings confirmed the higher capacity of OFR production by colonic cells with metabolic changes, as shown by the relationship between an increased production of OFR and the disruption of different defense systems of epithelial barrier. 13 Based on these findings, several studies began to test the effectiveness of substances with antioxidant activity for the treatment of DC.…”
Section: Discussionsupporting
confidence: 69%
“…Figure 4A) reflects the reduction in the number of mucus producing cells. Previous studies have shown that animals that had their fecal transit decreased, also had a decrease in the number of mucous cells, whic led to significant reduction in crypt depth (Mello et al, 2012). In the present investigation, it was also demonstrate an increase in crypt width (Figures 3A and B; Figure 4B) and epithelium height (Figure 3A and B; Figure 4C) in animals exposed to nickel chloride.…”
Section: Resultssupporting
confidence: 78%
“…Nutritional variations (Hermes et al 2008b) and the exclusion of intestinal transit (Mello et al 2012) lead to a reduction of the barrier formed by intestinal mucus on the mucosa of the large intestine in rats. In the colon, the mucus layer performs a lubricating function that facilitates the progression of fecal content and also provides protection against physical and chemical insult caused by microorganisms, toxins, and digestive enzymes in the intestinal lumen (Gaudier et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The mucus that covers the epithelium represents the first line of intestinal mucosal defense against the invasion of antigens and bacteria that are present in the colonic lumen (Corfield et al 2000, Mello et al 2012. The protective effect provided by mucus is related to the presence of mucins (i.e., glycoproteins synthesized and secreted by goblet cells) (Gaudier et al 2009).…”
Section: Introductionmentioning
confidence: 99%